Multi-level two-way cross-chain inventory coordination model that combines the same level with different levels in multi-supply chains. (November 2017) - Yan, Bo; Cai, Cong-Yan; Shi, Ping
A cross-chain inventory emergency replenishment model that comprises the enterprises of manufacturers, wholesalers, and retailers at the same level and at different levels based on a co-opetition relationship in cluster supply chains is constructed in this work. The model is built by studying two three-level supply chains that each comprises manufacturers, wholesalers, and retailers using the system dynamics method. Subsequently, the proposed cross-chain inventory collaboration model is compared with currently available models and then simulated using the system dynamics simulation software Vensim. Simulation results show that the proposed model further improves existing theoretical research achievements in the field both locally and abroad, thereby advancing theoretical research on cross-chain inventory collaboration. This study also provides decision-making references for the practice of inventory collaboration among enterprises in industrial clusters.